Effects of Suilysin on Streptococcus suis-Induced Platelet Aggregation - Zhang, Shengwei; Wang, Junping; Chen, Shaolong; Yin, Jiye; Pan, Zhiyuan; Liu, Keke; Li, Lin; Zheng, Yuling; Yuan, Yuan; Jiang, Yongqiang (Frontiers in Cellular and Infection Microbiology, 2016)
Blood platelets play important roles during pathological thrombocytopenia in streptococcal toxic shock syndrome (STSS). Streptococcus suis (S. suis) an emerging human pathogen, can cause STSS similarly to S. pyogenes. However, S. suis interactions with platelets are poorly understood. Here, we found that suilysin (SLY), different from other bacterial cholesterol-dependent cytolysins (CDCs), was the sole stimulus that induced platelet aggregation. Furthermore, the inside-out activation of GPIIb/IIIa of platelets mediated SLY-induced platelet aggregation. This process was triggered by Ca2+ influx that depend on the pore forming on platelets by SLY. Additionally, although SLY induced α-granule release occurred via the MLCK-dependent pathway, PLC-β-IP3/DAG-MLCK and Rho-ROCK-MLCK signaling were not involved in SLY-induced platelet aggregation. Interestingly, the pore dependent Ca2+ influx was also found to participate in the induction of platelet aggregation with pneumolysin (PLY) and streptolysin O (SLO), two other CDCs. It is possible that the CDC-mediated platelet aggregation we observed in S. suis is a similar response mechanism to that used by a wide range of bacteria. These findings might lead to the discovery of potential therapeutic targets for S. suis-associated STSS.